2008
DOI: 10.1080/13669870802261595
|View full text |Cite
|
Sign up to set email alerts
|

Emotion, affect, and risk communication with older adults: challenges and opportunities

Abstract: Recent research suggests that emotion, affect, and cognition play important roles in risk perception and that their roles in judgment and decision-making processes may change over the lifespan. This paper discusses how emotion and affect might help or hinder risk communication with older adults. Currently, there are few guidelines for developing effective risk messages for the world's aging population, despite the array of complex risk decisions that come with increasing age and the importance of maintaining g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 84 publications
2
43
0
Order By: Relevance
“…We posit that motivational changes in people's orientation towards gains and losses influence information processing and decision strategies. Complementing research on older decision makers' stronger reliance on affective information [Finucane, 2008], we hypothesize that the motivational orientation towards gains or losses may influence the kind of affective information (gain-vs. loss-related information) older adults rely on more.In sum, this review elaborates on how motivational changes in goal orientation associated with normal aging may affect the decision-making process. This paper is divided into six sections: (a) the dynamics of gains and losses in normal aging, (b) goal orientation across adulthood, (c) motivational factors in decision making, (d) gains and losses in decision making and aging, (e) key issues for future research, and (f) applied consequences.…”
mentioning
confidence: 99%
“…We posit that motivational changes in people's orientation towards gains and losses influence information processing and decision strategies. Complementing research on older decision makers' stronger reliance on affective information [Finucane, 2008], we hypothesize that the motivational orientation towards gains or losses may influence the kind of affective information (gain-vs. loss-related information) older adults rely on more.In sum, this review elaborates on how motivational changes in goal orientation associated with normal aging may affect the decision-making process. This paper is divided into six sections: (a) the dynamics of gains and losses in normal aging, (b) goal orientation across adulthood, (c) motivational factors in decision making, (d) gains and losses in decision making and aging, (e) key issues for future research, and (f) applied consequences.…”
mentioning
confidence: 99%
“…However, in late adulthood, when development has reached full maturity and life experiences, challenges, and wisdoms accumulate, factors such as life stories, narratives, and the search for meaning are likely to be more relevant and dominate how events are perceived (Gubrium, 2001;Kenyon, 2002;Kenyon, Clark, & de Vries, 2001;Randall, 2001). Consequently, the uniqueness of late-life gamblingrelated perceptions (McNeilly & Burke, 2000, 2002) has yet to be properly captured and capitalized on, particularly for the purpose of communicating messages about risk (Finucane, 2008). A key strength of the current study, therefore, is to fill part of this gap in knowledge, as well as the gap in understanding the perspective of non-treatment-seeking gamblers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was also observed that younger individuals showed greater negativity bias at neural and behavioral level whereas elderly did not increase the level of attention before a negative information. It is known that the age-related changes in cognitive abilities such as memory and processing speed as well as increased reliance on automatic and adaptive motivational processes in older adults focus more on affective information (especially positive), what can explain why older and younger adults respond differently to information about risk 3,37 . Regarding knowledge acquired during the task, only two studies conducted this analysis in which was found a significant difference between young and old, with young people showing better learning.…”
Section: Resultsmentioning
confidence: 99%
“…In aging it has been increasingly common the maintenance of a productive lifestyle, so that they continue facing complex decisions such as selection of financial options, managing their lifetimes, treatment of multiple diseases and the decision of how to live the following year in the best way. Understanding the decision-making process in the later stages of life, therefore, becomes extremely important [3][4][5] . The neural mechanisms involved in the decision-making process are a major target of research in the field of cognitive and behavioral neuroscience 6,7 .…”
Section: Introductionmentioning
confidence: 99%